World Bank Support for Social Safety Nets 2007-2013 : A Review of Financing, Knowledge Services, and Results - Andrews, Colin (World Bank Group, Washington, DC, 2014)
This review examines World Bank support to social safety nets between FY2007-13, including both financing and knowledge services. During this time period World Bank financing for safety nets totaled just over United States (U.S.) 12 billion dollars, 273 financing activities in 93 countries, the World Bank spent approximately U.S. 118 million dollars on 281 safety net studies and supported approximately 129 credible safety net impact evaluations covering in 24 countries. Among the 93 countries represented in the portfolio, 42 received little or no safety net support from the World Bank prior to FY2007. The growth in Bank support is especially notable during the period of the food, fuel, and financial crises. The analysis delves into these trends by region, type of intervention, and instruments involved. Finally, it delineates implications and outlook for the future based on lessons learned, results measured, and evaluative evidence.